Screening of hepatitis B and C viral infection, recognition of risk factors, and immunization of patients against hepatitis B virus: a module developed for effective hepatitis control - Ejaz, Samina; Abdullah, Iqra; Malik, Waqas Nazir; Anjum, Shazia; Ashraf, Muhammad; Akhtar, Naveed; Khan, Aurangzeb; Hameed, Yasir; Usman, Muhammad; Cheema, Usman; Sidiq, Safeena (Frontiers in Public Health, 2023)
The continually increasing incidence of hepatitis, a worldwide health issue, in Pakistan, highlighted the need to investigate the epidemiology factors and implement preventive measures accordingly. The purpose of this study was to scrutinize the prevalent and significantly associated risk factors of hepatitis in students and employees, screening them for hepatitis B and C virus and vaccinating them against HBV to make IUB hepatitis free. Methodology: A total of 12912 participants including students (n=10,948) and employees (n=1964) were screened for HBV and HCV via immunochromatographic test. Hepatitispositive participants' blood samples were further tested by quantitative PCR and viral load was estimated using quantitative PCR. All the hepatitis-negative participants were vaccinated against HBV. The demographic and risk factors-related data were collected using the questionnaire. Statistical analysis (Chi-square test and bivariate regression analysis) was performed using SPSS software to explore any association between risk factors and hepatitis. Results: Results indicated that 662/12912 participants (students=478/10,948, employees=184/1,964) were tested positive for hepatitis. Among them, HCV was observed to be more prevalent than HBV among the study participants, employees, and students, and viral count was low in both HBV and HCV-infected participants. However, males were more affected than females. The studied risk factors represented higher frequency among hepatitispositive participants relative to the hepatitis-negative participants. The Chi-square test revealed that students' gender, history of hepatitis in the family and relatives, dental treatment, and sharing cosmetics and shaving blades while in employees group surgery and age to be the significant (P>.005) risk factors of hepatitis. Moreover, the reuse of used syringes and the use of public washrooms were found to be associated with hepatitis in both groups. The bivariate analysis helped to identify various new risk factors which were independently, either positively or negatively, associated with hepatitis. Discussion: Our study enabled us to recognize different risk factors of hepatitis among the target population. The information thus generated can be usefully exploited in planning hepatitis awareness, targeted screening, and effective control programs for other target populations. In general, this module can be further exploited for any other disease.